Vitamin E TPGS Used as Emulsifier in the Preparation of Nanoparticulate Systems - Bernabeu, Ezequiel Adrian (2013)
In recent years, nanoparticulate systems have matured from simple devices to multifunctional and more complex systems. They are biodegradable, stable in blood, non-toxic, and non immunogenic construct, capable of delivering drugs in a specific site, thereby improving efficacy. Their capabilities as drug delivery system and the interaction with the biological cells in the target tissue are dependent on their physicochemical properties such as particles size, size distribution, surface charge and morphology. Polymeric nanoparticles are usually produced by two classical methods: nanoprecipitation and emulsion-solvent evaporation technique. In such process, a number of preparation parameters can affect the nature of the nanoparticles as: drug, polymer concentration, temperature, solvent volume, aqueous:organic phase ratio, type and concentration of emulsifier and so forth. One of the most important formulation parameters involves the emulsifier, which is necessary as surfactant stabilizer in the process to form nanoparticles. D-α-tocopheryl polyethylene glycol (PEG) 1000 succinate (TPGS) is a water soluble derivate of natural source vitamin E. It is amphipathic and hydrophilic, exhibiting the characteristics of a typical surface-active agent. This review summarizes recently available information regarding the emulsifying effects of TPGS on the preparation, characterization, in vitro release and in vivo performance of the nanoparticulate systems, and the advantages of TPGS-drug conjugates.